Association between sarcopenia and hemoglobin level: a systematic review and meta-analysis - Wang, Hui; Lin, Ping (Frontiers in Medicine, 2024)
Background Sarcopenia is a disease characterized by decreased skeletal muscle mass and function in elderly individuals. Decreased hemoglobin levels is a marker of anemia. According to reports, there may be an association between anemia and sarcopenia, but research is inconsistent. Therefore, this meta-analysis aims to explore the association between sarcopenia and low hemoglobin levels. Methods We searched PubMed, Embase, the Cochrane Library, Web of Science, Ovid, China National Knowledge Infrastructure (CNKI), and Wan Fang databases until September 2022. The present study included cross-sectional and case-control studies regarding low hemoglobin levels and sarcopenia. The studies were selected using inclusion and exclusion criteria. Studies were meta-analyzed by Review Manager 5.4 and Stata 16.0. We performed the heterogeneity test using the I2 test. Subgroup analysis was carried out to explore the cause of heterogeneity. Egger test was used to evaluate publication bias. Results Out of 1,550 initial studies, 16 studies were meta-analyzed. Sarcopenia participants had significantly lower levels of hemoglobin than controls (MD = −0.53, 95% CI: −0.68 to −0.37, p < 0.001). Subgroup analysis, performed in China population reported lower hemoglobin levels in the sarcopenia population (MD = −0.49, 95% CI: −0.65 to −0.33, p < 0.001). And sarcopenia based on AWGS criteria reported lower hemoglobin levels (MD = −0.49, 95% CI: −0.65 to −0.33, p < 0.001). Among the population from hospitals and communities, patients with sarcopenia have lower hemoglobin levels. Conclusion Our meta-analysis found evidence that sarcopenia is associated with low hemoglobin levels. However, further large-scale prospective studies should be conducted in the future to further confirm our conclusions. Systematic review registration PROSPERO, CDR42024532252.